Thermal analysis of a dry cooling method in a dental implant drilling procedure: an in vitro randomized study - Kubilay Baris; Meltem Hendek; Hatice Ebru Olgun (BMC Oral Health)
Abstract Background Excessive temperature rise during drilling can lead to thermal bone damage and compromise implant success. This in vitro study aimed to evaluate the effectiveness of the newly introduced “dry cooling” method to control heat generation during dental implant osteotomy using different hand pressure. Methods Standardized osteotomies (Ø4.1 mm, 10 mm depth) were performed on bovine rib bone blocks using two cooling methods—dry cooling (DC) and saline cooling (SC)—and two hand pressure levels: low pressure (LP) and high pressure (HP), resulting in four experimental groups (DC-LP = Group A, DC-HP = Group B, SC-LP = Group C, SC-HP = Group D; n = 30 per group). The DC setup employed a closed-loop thermoelectric system based on a Peltier module. Real-time temperature changes were recorded using thermocouples. Bone particles were weighed, and drilling time was measured. In statistical analysis, whether the data conformed to normal distribution was evaluated with the kurtosis-skewness test. The relationship between cooling method and hand pressure and temperature was evaluated with the ANOVA test. Tukey test was used for multiple comparisons. T-test was used for comparison between independent groups and the relationships between variables were analyzed with the Pearson correlation test. The statistical significance level in the study was determined as p < 0.05. Results Significant differences in temperature increase were observed between the groups (p < 0.001). Group A had the lowest temperature increase (2.00 ± 0.84 °C) and the lowest final temperature (23.41 ± 1.23 °C), while Group D had the highest temperature increase (5.45 ± 0.90 °C) and the highest final temperature (26.38 ± 1.03 °C). Bone particle yield differed significantly depending on the cooling method used (p < 0.001). Conclusions To prevent a temperature rise during dental implant osteotomy, DC may provide better temperature stabilization in specimens with high cortical content than external cooling with saline. Further studies are needed to optimize the effects of the DC method.